2014
DOI: 10.1007/s11266-014-9476-8
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenon of Staff Volunteering: How Far Can You Stretch the Psychological Contract in a Nonprofit Organization?

Abstract: In nonprofit organizations, hybrid activities that straddle both paid work and volunteering have been documented. However, conceptualization of these hybrid activities is missing. This article conceptualizes one kind hybrid activity-''staff volunteering'' (SV) in which self-selected, paid nonprofit employees, motivated by volunteerism, willingly volunteer to perform work that is perceived to be unpaid by the employee. SV enriches our understanding of volunteerism and the nature of nonprofit work by conceptuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Preston (1989) found nonprofit employees made 20% less than for-profit employees in similar roles, and when including fringe benefits, this cost differential increased to 40% (Emanuele, 1997). Some have explained the compensation differential by the willingness of employees to "donate" labor in the nonprofit sector, either through accepting sub-market wages (Rose-Ackerman, 1996) or donating their time beyond the hours they are compensated (Knutsen and Chan, 2014).…”
Section: Compensation Strategy In Nonprofit Contextsmentioning
confidence: 99%
“…Preston (1989) found nonprofit employees made 20% less than for-profit employees in similar roles, and when including fringe benefits, this cost differential increased to 40% (Emanuele, 1997). Some have explained the compensation differential by the willingness of employees to "donate" labor in the nonprofit sector, either through accepting sub-market wages (Rose-Ackerman, 1996) or donating their time beyond the hours they are compensated (Knutsen and Chan, 2014).…”
Section: Compensation Strategy In Nonprofit Contextsmentioning
confidence: 99%
“…Studies have shown that individuals preferring public and nonprofit careers over private sector employment exhibit greater altruistic behaviors, such as volunteering and donating time, blood, and money (Clerkin, Paynter, & Taylor, 2009; Houston, 2006; Knutsen & Chan, 2015; Lee, 2012; Pandey, Wright, & Moynihan, 2008). Researchers further note that the prosocial nature of public service satiates individual needs for meaningful and important work fueling their intrinsic work satisfactions.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…In addition, it is important to consider the conciliation of professional and personal lives [43,44] and the equal opportunities for all employees [32,42,[45][46][47]. In the line of social commitment, the participation of the organization in social projects [48,49] and the organization of volunteer activities in collaboration with NGOs [49,50], define new responsible actions in management.…”
Section: Introductionmentioning
confidence: 99%